The Bahamas. Significant achievements 2021 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Bahamas during 2021 are identified, with respect to the needs and interests of the country, strengthening sustainable development, biofertilizers, agrotourism, good agricultural practices, technology, resilience to climate change, soil management, food security and rum production. Likewise, work was done on economic development, food production, forestry and fishing. Finally, a pilot ICT application was carried out.